2011
DOI: 10.1038/nsmb.2147
|View full text |Cite
|
Sign up to set email alerts
|

An asymmetric interface between the regulatory and core particles of the proteasome

Abstract: The S. cerevisiae proteasome comprises a 19-subunit regulatory particle (RP) and 28-subunit core particle (CP). To be degraded, substrates must cross the CP-RP interface, a site of complex conformational changes and regulatory events. This interface includes two aligned heteromeric rings: the six ATPase (Rpt) subunits of the RP and the seven α subunits of the CP. Rpt C-termini bind intersubunit cavities of the α ring, thus directing CP gating and proteasome assembly. We used crosslinking to map the Rpt C-termi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
86
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(95 citation statements)
references
References 59 publications
(127 reference statements)
5
86
1
2
Order By: Relevance
“…However, this density is weaker than that observed in the α3/α4 and α1/α2 pockets. A recent cross-linking study, in which cysteines were introduced into the AAA-ATPase C termini, was consistent with our observations (23). Specifically, Rpt2 and Rpt3 were found to localize in the pockets formed by the CP α3/α4 and α1/α2 interfaces, respectively, whereas Rpt5 was not confined to a specific pocket and was found to occupy both α5/α6 and α6/α7 pockets.…”
Section: Aaa-atpase Hexamersupporting
confidence: 77%
See 1 more Smart Citation
“…However, this density is weaker than that observed in the α3/α4 and α1/α2 pockets. A recent cross-linking study, in which cysteines were introduced into the AAA-ATPase C termini, was consistent with our observations (23). Specifically, Rpt2 and Rpt3 were found to localize in the pockets formed by the CP α3/α4 and α1/α2 interfaces, respectively, whereas Rpt5 was not confined to a specific pocket and was found to occupy both α5/α6 and α6/α7 pockets.…”
Section: Aaa-atpase Hexamersupporting
confidence: 77%
“…The topological order of the AAA-ATPase subunits is Rpt1/Rpt2/ Rpt6/Rpt3/Rpt4/Rpt5, as determined based on protein-protein interactions (20) and engineered disulfide cross-links (21). Integration of a cryoelectron microscopy (cryo-EM) map at 9.1-Å resolution, protein-protein interactions, and site-specific intermolecular cross-links revealed the relative positions of the AAAATPase ring and the CP (20,22), which was subsequently corroborated by engineered disulfide cross-links between the AAAATPase C termini and residues in the pockets between the α-subunits of the CP (23). In contrast, the spatial configuration of the non-ATPase subunits and their role in the preparation of substrates for degradation remains largely unknown.…”
mentioning
confidence: 94%
“…Previous biochemical studies on the yeast proteasome suggested that the C termini of Rpt2, Rpt3, and Rpt5 contain conserved C-terminal HbYX motifs that insert into pockets formed between adjacent α-subunits (40,41). In the S A state, the HbYX motifs of both Rpt3 and Rpt5 insert into the α1-α2 and .…”
Section: Resultsmentioning
confidence: 99%
“…The principal channel-blocking tails are from α2 and α4; the α3-tail, which behaves as a lynchpin of the gate (44), is controlled by Rpt2 (Fig. 2N) (40). The reorientation of these tails constitutes gating and controls substrate entry into the CP.…”
Section: Resultsmentioning
confidence: 99%
“…The challenge will be to identify substrates degraded by one or more of these Cdc48-dependent mechanisms. Docking of C-terminal HbYX tripeptides into pockets on the periphery of the 20S α ring are important for 20S binding by archaeal PAN and the Rpt 1-6 unfolding ring of the 19S eukaryotic regulatory particle (10,19,21). HbYX-α interactions also help stabilize binding of Cdc48 to 20S, but archaeal Cdc48 still binds and functionally collaborates with 20S after deletion of this C-terminal tripeptide (4).…”
Section: Discussionmentioning
confidence: 99%